Electrospun nanofibers : an alternative sorbent material for solid phase extraction - Chigome, Samuel (Rhodes University, Faculty of Science, Department of Chemistry, 2012)
The work described in the thesis seeks to lay a foundation for a better understanding of the use of electrospun nanofibers as a sorbent material. Three miniaturised electrospun nanofiber based solid phase extraction devices were fabricated. For the first two, 10 mg of electrospun polystyrene fibers were used as a sorbent bed for a micro column SPE device (8 mm bed height in a 200 Î¼l pipette tip) and a disk (I) SPE device (5 mm 1 mm sorbent bed in a 1000 Î¼l SPE barrel). While for the third, 4.6 mg of electrospun nylon nanofibers were used as a sorbent bed for a disk (II) SPE device, (sorbent bed consisting of 5 5 mm 350 Î¼m stacked disks in a 500 Î¼l SPE barrel). Corticosteroids were employed as model analytes for performance evaluation of the fabricated SPE devices. Quantitative recoveries (45.5-124.29 percent) were achieved for all SPE devices at a loading volume of 100 Î¼l and analyte concentration of 500 ng ml-1. Three mathematical models; the Boltzmann, Weibull five parameter and the Sigmoid three parameter were employed to describe the break through profiles of each of the sorbent beds. The micro column SPE device exhibited a breakthrough volume of 1400 Î¼l, and theoretical plates (7.98-9.1) while disk (I) SPE device exhibited 400-500 Î¼l and 1.39-2.82 respectively. Disk (II) SPE device exhibited a breakthrough volume of 200 Î¼l and theoretical plates 0.38-1.15. It was proposed that the formats of future electrospun nanofiber sorbent based SPE devices will be guided by mechanical strength of the polymer. The study classified electrospun polymer fibers into two as polystyrene type (relatively low mechanical strength) and nylon type (relatively high mechanical strength).
Keywords: Nanofibers -- Research; Electrospinning -- Research; Sorbents -- Research; Extraction (Chemistry) -- Research